A Simple Method for Measuring Apoplast Hydration and Collecting Apoplast Contents. Issue 4 (1st March 2019) - Gentzel, Irene; Giese, Laura; Zhao, Wanying; Alonso, Ana Paula; Mackey, David
Abstract : A simple method allows calculation of apoplast hydration and efficient extraction of apoplast contents from maize seedling leaves. Abstract: The plant leaf apoplast is a dynamic environment subject to a variety of both internal and external stimuli. In addition to being a conduit for water vapor and gas exchange involved in transpiration and photosynthesis, the apoplast also accumulates many nutrients transported from the soil as well as those produced through photosynthesis. The internal leaf also provides a protective environment for endophytic and pathogenic microbes alike. Given the diverse array of physiological processes occurring in the apoplast, it is expedient to develop methods to study its contents. Many established methods rely on vacuum infiltration of an apoplast wash solution followed by centrifugation. In this study, we describe a refined method optimized for maize ( Zea mays ) seedling leaves, which not only provides a simple procedure for obtaining apoplast fluid, but also allows direct calculation of apoplast hydration at the time of harvest for every sample. In addition, we describe an abbreviated method for estimating apoplast hydration if the full apoplast extraction is not necessary. Finally, we show the applicability of this optimized apoplast extraction procedure for plants infected with the maize pathogen Pantoea stewartii ssp stewartii, including the efficient isolation of bacteria previously residing in the apoplast. The approaches to establishing this method should make it generally applicable to other types of plants.